Reproduction barrier between two lineages of bed bug (Cimex lectularius) (Heteroptera: Cimicidae) - Wawrocka, Kamila; Balvín, Ondřej; Bartonička, Tomáš (Parasitology research, 2015)
Populations of bed bugs, Cimex lectularius, have increased in recent years spreading into numerous urban areas across the Western world and making them an increasingly important pest of the twenty-first century. Research into hybridization within and between different lineages of bed bugs can help us to understand processes of micro- and macro-evolution in these ectoparasites and may inform the control of this pest species. Hybridization experiments between two host lineages of bed bug (C. lectularius) from Central Europe (Czech Republic), those associated with humans and those with bats, were conducted under laboratory conditions. Number of eggs and early instars were compared between crosses of mixed host lineages (interspecific mating) with pairs from the same host lineage, those from the same locality and same lineage from different localities (intraspecific mating). While crosses within host lineages resulted in egg production and later instars, crosses between different host lineages were unsuccessful, although of the mated females possessed sperm in their mesospermaleges and/or seminal conceptacles. These crosses did not even result in egg production. Moreover, in the mixed lineage crosses, mortality rates in adults were higher (51 and 50% higher in bat and human lineage, respectively) than in those animals from the same lineage. Survival of adults was in pairs from the same locality slightly higher than in pairs from different localities and differed statistically. These results support the existence of post-mating barriers and show reproductive isolation between two lineages of C. lectularius. Bat and human host adaptations can promote evolving of such barriers and can be product of alloxenic speciation.
Keywords: Chiroptera; hybridizace genetická; štěnice; rozmnožování; Bedbugs; ženské pohlaví; Reproduction; zvířata; Humans; Host Specificity; Female; infestace ektoparazity; hostitelská specificita; Hybridization, Genetic; Ectoparasitic Infestations; lidé; Animals